Problems of Testing in Teaching A Foreign Language to Students of Secondary Schools - Mamedova Madina Ashuralievna; Bakayeva Kamola Muminovna (Genius Journals, 2023)
In domestic and foreign pedagogy, an important place is occupied by the problems of monitoring learning outcomes. Currently, in the field of education, a new system for monitoring and evaluating students' educational achievements is being widely developed, focused on the widespread use of pedagogical tests. The relevance and importance of the development of test methods are determined by their technological capabilities, which make it possible to obtain objective information about the quality of training of students and contribute to the implementation of the competitiveness of the quality of education
Keywords: test tasks; verification tasks; evaluation and control system